2013
DOI: 10.1159/000354542
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Consequences of Bronchopulmonary Dysplasia in Prematurely Born Preschool Children

Abstract: Background: A limited number of studies have reported various short-term cardiovascular changes in bronchopulmonary dysplasia (BPD) patients in the postsurfactant era. Little is known about the course of these changes in children with BPD. Objectives: It was the aim of this study to investigate cardiovascular consequences of BPD at preschool ages and to find out possible risk factors related to cardiovascular sequelae. Methods: Prematurely born children with (n = 21) and without BPD (n = 20) were evaluated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 21 publications
2
33
0
2
Order By: Relevance
“…These give rise to an increase in pulmonary vascular resistance, which in turn leads to the onset of pulmonary arterial hypertension. This has often been associated with higher morbidity and mortality in BPD infants, especially in the first 6 months after a diagnosis of pulmonary arterial hypertension [30]. This diagnosis is thus important, not only for prognostic purposes but also to ensure appropriate treatment [31,32].…”
Section: Clinical Aspects and Functional Course Of Bpd With Agementioning
confidence: 99%
See 1 more Smart Citation
“…These give rise to an increase in pulmonary vascular resistance, which in turn leads to the onset of pulmonary arterial hypertension. This has often been associated with higher morbidity and mortality in BPD infants, especially in the first 6 months after a diagnosis of pulmonary arterial hypertension [30]. This diagnosis is thus important, not only for prognostic purposes but also to ensure appropriate treatment [31,32].…”
Section: Clinical Aspects and Functional Course Of Bpd With Agementioning
confidence: 99%
“…Echocardiography is recommended as the main screening tool, especially for BPD infants with an atypical clinical course. Cardiac catheterization can assess the severity of pulmonary arterial hypertension more accurately, but is generally only performed in more severe cases requiring vasodilators other than oxygen [30]. Pulmonary vascular reactivity to hypoxia may persist, and the negative effects of BPD on the global cardiac performance of both ventricles and on pulmonary arterial pressure may persist right up to preschool age [30].…”
Section: Clinical Aspects and Functional Course Of Bpd With Agementioning
confidence: 99%
“…We found reduced global LV systolic deformation in children in the longitudinal but not circumferential or radial dimensions. An increase in LV myocardial performance index that reflects impaired global systolic and diastolic function has also been reported in these children [12], [13]. Intriguingly, a recent study of adults born preterm revealed smaller LV diameters and reduced LV systolic and diastolic deformation but with preserved LV ejection fraction compared with those born at term [15].…”
Section: Discussionmentioning
confidence: 93%
“…Using tissue Doppler imaging, Yates et al [12] reported an increased tricuspid E/e ratio suggestive of increased RV end-diastolic pressure, while Koroglu et al [13] reported on reduced tricuspid systolic diastolic annular velocities and increased RV myocardial performance consistent with impaired global systolic and diastolic RV function in children with BPD. Our tissue Doppler findings in children with a history of BPD agree with those reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Jest przyczyną przewlekłych zaburzeń ogólnoustrojowych, przede wszystkim kardiologicznych, płucnych i neurologicznych [2][3][4][5]. Uważa się, że dzieci z tą chorobą są szczególnie narażone na rozwój astmy oskrzelowej, retinopatii, nadciśnienia systemowego, przerostu lewej komory serca, zaburzenia krążenia wieńco-wego, miopatii oraz na występowanie zespołu nagłej śmierci niemowlęcia [6][7][8]. Okresem ,,krytycznym'' w życiu takiego dziecka są wprawdzie pierwsze dwa lata życia, lecz problemy rozwojowe i zwiększona podatność na zakażenia dróg oddechowych, większa niż u dzieci zdrowych, utrzymują się przez kilka następnych lat [9,10].…”
unclassified